ASSEMBLY OF HIGH PRIVATE VARIETY CHILI: GENETIC VARIABILITY AND HERITABILITY GROWTH CHARACTER AND RESULTS - Eko Fransisko (SINTA Journal (Science, Technology, and Agricultural), 2020)
Limitations in obtaining superior varieties of red chili that are suitable to be planted in the highlands are one of the causes of the low yield of red chili in Rejang Lebong Regency. However, the availability of red chili germplasm as a genetic resource (SDG) in Rejang Lebong Regency is a good potential to be utilized to overcome problems in increasing the yield of red chili plants through the assembly of superior varieties. Assembling superior varieties of red chili has been done by researchers in order to get the desired plant character. This study aims to obtain information on the variability and heritability of growth character and yield of 18 red chili varieties in Rejang Lebong Regency. This research activity is the initial activity of developing the potential of germplasm that will be carried out so as to be able to overcome the problems in increasing the production of red chili in Rejang Lebong Regency. A series of research activities will produce superior varieties of red chili specifically for the highlands. The material used in this study was eighteen (18) varieties of chilli collections from various regions. The experimental design used was a Complete Randomized Block Design (RCBD) with a single factor, namely red chili plant varieties. The red chili varieties to be investigated for genetic variability and heritability in this study amounted to 18 and each treatment was repeated three times. The results showed that the highest estimated heritability was indicated by the leaf width variable at 96.69% and all observed variables had broad genotypic and phenotific variability.